Pengembangan Perangkat Pembelajaran dengan Strategi dan Metode Pembelajaran dalam PAI - Nurhadipah Nurhadipah; Messy Precia; Gusmaneli Gusmaneli (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This study aims to analyze various learning strategies and methods used in the development of PAI learning tools. This writing uses the library research method, which is a research approach that relies on data sources from various literatures such as books, scientific journals, articles, and other writings relevant to the topic. The research method used in this literature study is a descriptive qualitative approach, which aims to collect, analyze, and synthesize various literature regarding the development of learning tools with learning strategies and methods in Islamic Religious Education. The results of this study indicate that the development of Islamic Religious Education learning tools, such as syllabus, lesson plans, LKPD, and modules, needs to be designed to cover the cognitive, emotional, and spiritual aspects of students. Learning strategies should be varied and appropriate to students' characteristics, including direct, indirect, interactive, experiential, and independent strategies. A systematic and participatory approach allows educators to guide students to understand and practice religious values. Effective learning methods, such as lectures, discussions, assignments, and projects, encourage students to actively participate, think critically, and apply religious values in daily life.